Montelukast has no ergogenic effect on cycle ergometry in cold temperature - Rundell, K. W.; Spiering, B. A.; Baumann, J. M.; Evans, T. M. (Medicine & Science in Sports & Exercise, 2004)
Purpose: To examine the effects of a single 10-mg dose of ML on physical performance in EIB- and EIB+ athletes.